Computer Safety, Reliability, and Security 31st International Conference, SAFECOMP 2012, Magdeburg, Germany, September 25-28, 2012. Proceedings - Ortmeier, Frank; Daniel, Peter; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 31st International Conference on Computer Safety, Reliability, and Security, SAFECOMP 2012, held in Magdeburg, Germany, in September 2012. The 33 revised full papers presented were carefully reviewed and selected from more than 70 submissions. The papers are organized in topical sections on tools, risk analysis, testing, quantitative analysis, security, formal methods, aeronautic, automotive, and process. Also included are 4 case studies.
Tools -- Risk Analysis -- Testing -- Quantitative Analysis -- Security -- Formal Methods -- Aeronautic -- Automotive -- Process -- Case Studies.
Keywords: Computer science; Computer Communication Networks; Software engineering; Data protection; Computer software; Computer Science; Systems and Data Security; Computer Communication Networks; Software Engineering; Algorithm Analysis and Problem Complexity; Computers and Society; Special Purpose and Application-Based Systems